SP9.1.7 Emergency Laparotomy for Trauma in the United Kingdom and Ireland: a Prospective Multicentre Study. (28th October 2021) - Vulliamy, Paul; Marsden, Max; Carden, Richard; Brohi, Karim; Davenport, Ross; ,
Abstract: Aims: Trauma patients requiring abdominal surgery have significant morbidity and mortality, but are not included in existing national audits of emergency laparotomy. The aim of this study was to examine processes of care and outcomes among trauma patients undergoing emergency abdominal surgery in the UK and Ireland. Methods: A prospective trainee-led multicentre audit was conducted over six months from January 2019 across the national trauma system. Patients undergoing laparotomy or laparoscopy within 24 hours of injury were included. Subgroup analysis was conducted in those requiring major haemorrhage protocol (MHP) activation. Results: The study included 363 patients from 34 hospitals (22 major trauma centres). The majority were young males with no co-morbidities who required surgery for control of bleeding (51%) or exploration of penetrating injuries (46%). Over 85% received consultant-led care in the emergency department (318/363) and operating theatre (321/363). The MHP subgroup made up 45% of the cohort but accounted for 97% of deaths and 79% of ICU days, with a mortality rate of 19% and a massive transfusion rate of 32%. Compared to non-MHP patients they had shorter times to theatre (122 vs 218 minutes, p < 0.001), higher rates of advanced prehospital care (60% vs 33%, p < 0.001) and higher rates of consultant-led care (95% vs 85%, p < 0.001). Conclusion: The majority of trauma patients requiring emergency abdominal surgery receive consultant-delivered perioperative care which is appropriately tailored to patient risk profile. Despite this, mortality and resource utilization among high-risk patients remains substantial, justifying ongoing performance improvement initiatives and research into novel therapeutics.